Analysis and improvement of an identity-based signature scheme from lattices - ANGChun-li Y; ANJian-hua Y; HENGShi-hui Z; ANGLi-cheng W; ANGYu Y (Tongxin xuebao)
Liu et al proposed an identity-based signature from lattices in 2013,and proved that it can achieve strong un-forgeability in the standard model.Through analysis,the security proof of this scheme has some defect,and then show that the scheme cannot prove the strong unforgeability under selective identity and adaptive chosen-message attacks.Then,using Boyen signing technique (PKC 2010) inpoves the signing algorithm,and proves the strong unforgeability under selective identity and adaptive chosen-message attacks (SU-sID-CMA) in the standard model.In addition,it com-pares the efficiency and security of the scheme and the other identity-based signatures from lattices.